IMPLEMENTATION OF ACTIVITY-BASED COSTING FOR ACCURATE STUDY PROGRAMME COST CALCULATION AT X UNIVERSITY - Lilis Binawati (Universitas 17 Agustus 1945 Surabaya, 2026)
The importance of implementing Activity-Based Costing (ABC) in accurately calculating the cost of higher education study programmes was considered crucial in supporting managerial decision-making, particularly in determining the tuition fees (SPP) per semester for students while accommodating the development of hybrid learning systems. The implementation of Activity-Based Costing at University X aimed to transform a traditional cost allocation system into a more accurate costing system for educational services charged to students. The method was expected to alleviate the primary issue of cost distortion, as ABC allocates costs based on activities and the resources consumed that are directly related to educational, educational support, and non-educational activities. This study employed a qualitative approach in which the researcher acted as a participant observer. The researcher directly identified, analysed, and allocated the costs of supporting unit activities to the main academic units. The analysis also included the costs related to the implementation of the hybrid blended learning system at University X using the ABC approach. The accuracy of calculating the prime cost of each study programme depends on cost traceability, which was conducted through three tracing methods: direct tracing, driver tracing, and allocation. The results show that the implementation of ABC increases the accuracy of calculating the prime cost of each study programme at University X. The analysis identifies cost distortions in the form of overcosting and undercosting and indicates the presence of cross-subsidisation between study programmes. These findings provide more reliable cost information for university management in determining tuition-related policies.